2015
DOI: 10.1007/s12282-015-0585-z
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of simultaneous oncoplastic breast surgery in patients with locally advanced breast cancer

Abstract: Oncoplastic techniques are suitable and safe for patients undergoing OBCS. These techniques do not pose a risk to oncological local control. No survival or follow-up problems were detected during the 5-year follow-up period, the esthetic results were acceptable, and the satisfaction rate was high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 30 publications
3
23
0
Order By: Relevance
“…The complication rates reported in the literature vary between 10 to 91% in the reduction mammoplasty operations performed for both malignant and benign reasons (8)(9)(10)(11)(12)(13). A recent systematic review of OBCS reported postoperative complications occurred in 14.3% of patients, including liponecrosis 3.3%, skin necrosis 0.5%, hematoma 2.5%, seroma 1.0%, delayed wound healing 2.2%, nipple necrosis 0.4% and/or infection 1.9% (14).…”
Section: Discussionmentioning
confidence: 99%
“…The complication rates reported in the literature vary between 10 to 91% in the reduction mammoplasty operations performed for both malignant and benign reasons (8)(9)(10)(11)(12)(13). A recent systematic review of OBCS reported postoperative complications occurred in 14.3% of patients, including liponecrosis 3.3%, skin necrosis 0.5%, hematoma 2.5%, seroma 1.0%, delayed wound healing 2.2%, nipple necrosis 0.4% and/or infection 1.9% (14).…”
Section: Discussionmentioning
confidence: 99%
“…Mathes et al [18] operated 17 patient with LABC utilizing advanced oncoplastic techniques with no positive margins, Similary Viera et al [16] reported margin length 16.44 mm by oncoplastic surgery with no positive margins, Emiroglu et al [14] found that the mean surgical margin length was 8.7 mm (range 5 -17 mm) with positive margins in 7.1% of cases, in a study done by Clough et al [21] patients who received NACT and OS had a positive margins rate 10.9%.…”
Section: Discussionmentioning
confidence: 99%
“…The mean follow up was 1.7 years with 2 cases had local recurrence (LR) (one had triple negative tumor and the other was Her-2+), Within 61 months follow up Emiroglu et al [14] had 14.6% local recurrence, Regano [19] reported 1 case with LR during 32 months follow up, 2 cases had LR within 60 months follow up in study of Viera [16], Specht and Gralow [15] reported no LR in 15 months follow up, mean follow-up was 72.8 months. Ipsilateral local and locoregional recurrence were 11.2% and 15.3% respectively in the study published by Carrrara in 2017 [13].…”
Section: Discussionmentioning
confidence: 99%
“…If the skin is closed directly, breast deformity or dislocation of the nipple-areolar complex may occur (8). Oncoplastic surgical techniques are necessary to achieve good cosmetic outcomes from BCS (8,9).…”
Section: Introductionmentioning
confidence: 99%